Modelling temperature effects on ammonia-oxidising bacterial biostability in chloraminated systems - Sarker, Dipok; Sathasivan, Arumugam; Joll, Cynthia; Heitz, Anna (Elsevier, 2013)
The biostability concept has been successfully used to predict the onset of nitrification in drinking water distribution systems, but in certain cases deficiencies have been observed in the predictions, indicating that modifications to parameters were needed. At the biostable disinfectant residual concentration (BRC), the rate of ammonia-oxidising bacterial (AOB) growth due to the substrate (free ammonia) and the rate of inactivation due to the disinfectant are balanced. Growth and inactivation rates vary greatly with temperature, but temperature is yet to be considered in the biostability equation. In this paper, two separate novel models are proposed which take into account the temperature effects on the biostability equation. First, a novel model of specific growth rate variability with temperature was shown to be valid for different bacterial species. Then, the biostability model was modified and validated for ammonia-oxidising bacterial activity using data collected from laboratory and full-scale distribution systems. The proposed model has two important uses: while the specific growth rate model and biostability model can be widely adopted for many microbes, the biostability model for AOB also has the potential to aid water utilities in disinfectant residual management throughout yearly temperature variations.